Mediating role of social media in tourist destination decision-making: influence and trends - Arispe, Virgilia J.; Javier, Joan Valerie G.; Pangilinan, Katherine Marie G. (Jurnal Studi Komunikasi, 2025)
Social media plays a significant role in influencing travel decisions in today’s digital landscape. This study examines how various aspects of social media specifically content types (videos, images), user feedback (comments), and engagement metrics (likes, shares) impact tourists’ decision-making processes, grounded by the AIDA model. A purposive sample of 200 tourists participated in an online survey via Google Forms across the Philippines Archipelago. Findings revealed that videos were the most influential feature across all decision-making stages: catching attention, generating interest, building desire, and prompting action. In contrast, likes received the lowest influence, although still impactful. The results highlight the significance of video content in travel marketing, suggesting that marketers should prioritise producing creative, authentic, and engaging travel videos to establish trust and effectively guide tourists through their decision-making process. This research underscores the growing value of user-generated video content as a powerful tool in driving tourist engagement and travel behaviour.